2015
DOI: 10.1097/qad.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of their HIV status to perinatally infected youth using the adapted Blasini disclosure model in Haiti and the Dominican Republic

Abstract: Objectives To assess the safety, acceptability, and preliminary efficacy of a culturally-adapted disclosure intervention for perinatally HIV-infected combined antiretroviral therapy patients in Haiti and the Dominican Republic. Design A quasi-experimental trial was conducted comparing caregiver–youth pairs who completed the intervention [adapted Blasini disclosure model (aBDM)] to pairs who discontinued aBDM participation before disclosure. aBDM consists of five components: structured healthcare worker train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Task shifting pediatric testing discussions to peer mentors—other adults who have tested their children—may be effective [28]. Disclosure remains delayed in many settings [29-32] and family disclosure interventions may complement pediatric testing scale-up [27, 33-37]. …”
Section: Discussionmentioning
confidence: 99%
“…Task shifting pediatric testing discussions to peer mentors—other adults who have tested their children—may be effective [28]. Disclosure remains delayed in many settings [29-32] and family disclosure interventions may complement pediatric testing scale-up [27, 33-37]. …”
Section: Discussionmentioning
confidence: 99%
“…The resources available for training providers in these countries about paediatric HIV disclosure are largely based on the Western disclosure model and experience . While some models guiding disclosure have been implemented within research settings in LMICs , the depth of implementation of such models for HIV status disclosure in resource‐limited, routine clinical care is unclear. Documenting existing strategies for the HIV disclosure process in these settings would help to characterize the current limits and strengths to HIV disclosure process, so that these data could be used to develop supportive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies address the design and evaluation of paediatric HIV status disclosure interventions. Beck-Sague et al [36] reported promising results of an ongoing quasi-experimental trial of a culturally adapted paediatric HIV disclosure intervention in Haiti, which included healthcare worker training, education for youth, capacity-strengthening for caregivers, a scheduled disclosure session and postdisclosure support for care-givers and youth. Equally reporting on an ongoing study, Reynolds et al [37] presented the background, process and methods of a collaborative approach to develop and evaluate a paediatric HIV disclosure intervention in Ghana; challenges and implications are also reported.…”
mentioning
confidence: 99%